2005
DOI: 10.1007/s10646-004-6373-8
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impacts of Diesel Fuel on Bacteria and Phytoplankton in a Tropical Estuary Assessed Using In Situ Mesocosms.

Abstract: Dissolved or dispersed petroleum hydrocarbon concentrations (DDPH) were monitored in Ponggol estuary, Singapore, fortnightly from July 1999 to June 2000. DDPH concentrations ranged from 4.4 to 248.9 microg l(-1) and 0.4 to 1099.7 microg l(-1) for surface and subsurface waters, respectively and with mean concentrations of 41.01 microg l(-1) in the water column. Absorbed or adsorbed petroleum hydrocarbon (AAPH) concentrations measured in sediments ranged from 20.6 to 541.0 mg kg(-1), with mean concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
14
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 60 publications
5
14
1
Order By: Relevance
“…Pigment analyses confirmed such a change in exposed communities; diatoms were left to dominate the 250 nmol l -1 community together with green algae, whereas prymnesiophytes and cryptophytes declined compared to the control community. This is in contrast to other findings, in which diatoms were found to be more sensitive to a mixture of hydrocarbon compounds than other algal groups (Nayar et al 2005, Sargian et al 2005. The discrepancy may be caused by the more complex contamination used in those studies, or to the 'rough' characterisation of phytoplankton communities by the pigment analyses used in this study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Pigment analyses confirmed such a change in exposed communities; diatoms were left to dominate the 250 nmol l -1 community together with green algae, whereas prymnesiophytes and cryptophytes declined compared to the control community. This is in contrast to other findings, in which diatoms were found to be more sensitive to a mixture of hydrocarbon compounds than other algal groups (Nayar et al 2005, Sargian et al 2005. The discrepancy may be caused by the more complex contamination used in those studies, or to the 'rough' characterisation of phytoplankton communities by the pigment analyses used in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…Unfortunately, no microscopy data were available to verify the development of the diatom community. Towards the end of the mesocosm experiment, blue-green algae increased in the exposed communities, compared to the control community; this observation is consistent with other studies of PAH effects on phytoplankton (Bastian & Toetz 1985, Nayar et al 2005, in which cyanobacteria have been reported to be more tolerant to PAH exposure.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Diatoms dominated the communities after pyrene exposure at the expense of cryptophytes and dinoflagellates, which were more sensitive to pyrene. These results are consistent with our previous study (Hjorth et al 2007), but contrary to other findings (Nayar et al 2005, Sargian et al 2005. The combination of low total photosynthetic activity and high algal specific activity up until Days 4 through 5 for Py and NuPy communities usually suggests a shift in species composition towards more tolerant species (Hjorth et al 2007).…”
Section: Discussionsupporting
confidence: 91%
“…Since microalgae are primary producers of oxygen and are a vital food source for other organisms, the effects of oil spills and cleanup efforts can greatly influence the overall status of the aquatic ecosystem (Nayar et al 2005;Gonzalez et al 2009;Gilde and Pinckney 2012). Among the microalgae with established culture techniques and a history of use in toxicity tests is Tetraselmis spp.…”
mentioning
confidence: 99%